A stable AKD-in-water emulsion: Stabilized by MSG-modified laponite nanoparticle. Issue 7 (3rd July 2017) - Chen, Xueshuai; Wang, Huili; Liu, Wenxia; Li, Guodong; Yu, Dehai; Song, Zhaoping
ABSTRACT: Alkyl ketene dimmer (AKD) is widely used in papermaking industry, which is applied in form of o/w emulsion to increase paper water-resistance. In this paper, AKD-in-water emulsions were prepared by monosodium glutamate (MSG)-modified laponite. The aggregation, surface charge, and hydrophobicity of the laponite particles in aqueous dispersion were changed by the MSG and the properties of the as-prepared emulsions were varied correspondingly. When the MSG concentration is 2 mmol/g, AKD emulsion with small droplet size, high storage stability, and high sizing efficiency is obtained. The morphology, droplet diameter and distribution, storage stability and sizing efficiency of the AKD-in-water emulsion were investigated. GRAPHICAL ABSTRACT: